2004
DOI: 10.1103/physrevlett.92.176101
|View full text |Cite
|
Sign up to set email alerts
|

Bridging the Gap between Macro- and Nanotribology: A Quartz Crystal Microbalance Study of Tricresylphosphate Uptake on Metal and Oxide Surfaces

Abstract: We report a quartz crystal microbalance study of the nanodynamical properties of tricresylphosphate (TCP) reaction films formed on high purity Fe, Cr, Fe oxide, and Cr oxide surfaces at elevated temperatures. The data reveal trace levels of interfacial slippage, potentially in conjunction with viscoelastic effects, for reaction films characterized by very low macroscopic friction coefficients. In contrast, rigidly attached TCP reaction films are observed in systems characterized by high macroscopic friction co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Many studies aimed at elucidating the reaction mechanism of TBP, TCP and related compounds have been performed using different surface analytical techniques [20,21], including temperature-programmed reaction spectroscopy (TPRS) -often in combination with AES, both on clean iron surfaces [22] and on oxidized iron [23], and more recently using a quartz crystal microbalance [24,25]. These studies provided evidence that in the cases of TBP and TCP the film formation takes place following breakage of the C-O bond for the alkyl class and via P-O bond scission in the case of the aryl class.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies aimed at elucidating the reaction mechanism of TBP, TCP and related compounds have been performed using different surface analytical techniques [20,21], including temperature-programmed reaction spectroscopy (TPRS) -often in combination with AES, both on clean iron surfaces [22] and on oxidized iron [23], and more recently using a quartz crystal microbalance [24,25]. These studies provided evidence that in the cases of TBP and TCP the film formation takes place following breakage of the C-O bond for the alkyl class and via P-O bond scission in the case of the aryl class.…”
Section: Introductionmentioning
confidence: 99%
“…This is beyond the scope of our paper. Krim et al have shown that favorable macroscopic tribological properties from a mobile lubricant corresponded to a non-zero slip time value on a QCM; poor macroscopic tribological properties occurred when QCM slip time values were zero [24,25]. The QCM measurements showed that TCP possessed a non-zero slip time on PFTS, suggesting that TCP may in fact be mobile on the surface of PFTS.…”
Section: Discussionmentioning
confidence: 96%
“…By heating TCP, the vapor pressure is raised enough to condense a lubricating layer on exposed surfaces. The low vapor pressure under ambient conditions and ability to condense a lubricant film on a surface without significant line-of-sight limitations makes TCP a candidate of interest for MEMS lubrication to increase performance over chemically bound monolayer films [22][23][24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are not, however, particularly wear resistant, and decompose at 450°C (in vacuum) or lower, depending upon the environment [3]. Tricresylphosphate (TCP) and t-butyl phenyl phosphate (TBBP) are vaporphase organophosphate lubricants that are highly effective in preventing wear and oxidation in high-temperature macroscopic applications [4][5][6][7]. They were suggested for MEMS applications as early as 1998 [8].…”
Section: Introductionmentioning
confidence: 99%